Access to HIV care in the context of universal test and treat: challenges within the ANRS 12249 TasP cluster‐randomized trial in rural South Africa. Issue 1 (1st June 2016) - Plazy, Mélanie; Farouki, Kamal El; Iwuji, Collins; Okesola, Nonhlanhla; Orne‐Gliemann, Joanna; Larmarange, Joseph; Lert, France; Newell, Marie‐Louise; Dabis, François; Dray‐Spira, Rosemary; ,
Abstract : Introduction: We aimed to quantify and identify associated factors of linkage to HIV care following home‐based HIV counselling and testing (HBHCT) in the ongoing ANRS 12249 treatment‐as‐prevention (TasP) cluster‐randomized trial in rural KwaZulu‐Natal, South Africa. Methods: Individuals ≥16 years were offered HBHCT; those who were identified HIV positive were referred to cluster‐based TasP clinics and offered antiretroviral treatment (ART) immediately (five clusters) or according to national guidelines (five clusters). HIV care was also available in the local Department of Health (DoH) clinics. Linkage to HIV care was defined as TasP or DoH clinic attendance within three months of referral among adults not in HIV care at referral. Associated factors were identified using multivariable logistic regression adjusted for trial arm. Results: Overall, 1323 HIV‐positive adults (72.9% women) not in HIV care at referral were included, of whom 36.9% ( n =488) linked to care <3 months of referral (similar by sex). In adjusted analyses ( n =1222), individuals who had never been in HIV care before referral were significantly less likely to link to care than those who had previously been in care (<33% vs. >42%, p <0.001). Linkage to care was lower in students (adjusted odds‐ratio [aOR]=0.47; 95% confidence interval [CI] 0.24–0.92) than in employed adults, in adults who completed secondary school (aOR=0.68; CI 0.49–0.96) or at least some secondary school (aOR=0.59; CI 0.41–0.84) versus ≤ primary school, in those who lived at 1 to 2 km (aOR=0.58; CI 0.44–0.78) or 2–5 km from the nearest TasP clinic (aOR=0.57; CI 0.41–0.77) versus <1 km, and in those who were referred to clinic after ≥2 contacts (aOR=0.75; CI 0.58–0.97) versus those referred at the first contact. Linkage to care was higher in adults who reported knowing an HIV‐positive family member (aOR=1.45; CI 1.12–1.86) versus not, and in those who said that they would take ART as soon as possible if they were diagnosed HIV positive (aOR=2.16; CI 1.13–4.10) versus not. Conclusions: Fewer than 40% of HIV‐positive adults not in care at referral were linked to HIV care within three months of HBHCT in the TasP trial. Achieving universal test and treat coverage will require innovative interventions to support linkage to HIV care.